The Impact and Influencing Path of the Pilot Carbon Emission Trading market——Evidence From China - Xu, Wangzi (Frontiers in Environmental Science, 2021)
As the country with the largest CO2 emissions in the world, China has great pressure on emission reduction. The Chinese government has clearly put forward the goals of hitting peak carbon emissions by 2030 and carbon neutralization by 2060, Thus, China started the pilot carbon emission trading since 2013,which is an important policy tool to achieve energy conservation, emission reduction and low-carbon development ,and in July 2021 China opened the national carbon trading, which is the largest carbon market around the world. Therefore it is very important for China to study the role and mechanism of carbon trading at present. Based on the quasi-natural experiment of China's carbon market pilot, this paper uses panel data of 30 provinces and autonomous regions in Chinese mainland from 2008 to 2019, and conducts an empirical study on carbon emission reduction and economic effects of China's pilot provinces through Time-varying Differences-in-Differences method (Time-varying DID) model. The results show that the implementation of carbon trading policy can significantly inhibit carbon emissions and promote economic growth. At the same time, this paper further analyzes the emission reduction mechanism of the carbon emission trading policy through the intermediary effect test, and finds that the policy mainly realizes carbon emission reduction by changing the energy consumption structure, promoting low-carbon innovation and upgrading the industrial structure. In addition, innovative research has found the impact of carbon price signal and marketization on the emission reduction effect of carbon market. Finally, targeted suggestions are put forward.